Performance of reinforced concrete T beams strengthened in shear with NSM CFRP laminates - Dias, Salvador J. E. (2010)
The effectiveness of the Near Surface Mounted (NSM) technique with Carbon Fiber Reinforced Polymer (CFRP) laminates for the shear strengthening of T cross section Reinforced Concrete (RC) beams was assessed by experimental research. Three inclinations of the laminates were tested (45 , 60 and 90 ) and, for each one, three percentages of CFRP were adopted. The RC beams withNSMlaminates had a percentage of steel stirrups of 0.10%. The highest percentage of laminates was designed to provide a maximum load similar to that of a reference RC beam with a steel stirrup reinforcement ratio of 0.28%. The results showed that: inclined laminates were more effective than vertical laminates; an increase of the percentage of laminates produced an increase of the shear capacity of the beams; the contribution of the laminates for the beam shear resistance was limited by the concrete tensile strength; the failure modes of the beams were influenced by the percentage of the laminates. For each percentage of laminates, a homologous RC beam strengthened with U-shaped CFRP wet layup sheets (discrete strips) applied according to the Externally Bonded Reinforcement (EBR) technique was also tested, with the purpose of comparing the effectiveness of these two CFRP strengthening techniques. NSM was the most effective, not only in terms of increasing beam shear resistance but also in assuring better utilization of the tensile strength of the CFRP material. Except for the beams with the highest percentage of CFRP, the NSM technique was more effective than the EBR technique in terms of deformation capacity at beam failure. The ACI and fib analytical formulations have predicted a larger contribution of the EBR shear strengthening systems than the values recorded experimentally. The formulation provided by Nanni et al. for the NSM technique predicted a CFRP contribution around 61% of the experimentally registered values.